Crystal structure of rivastigmine hydrogen tartrate Form I (Exelon®), C14H23N2O2(C4H5O6). Issue 2 (8th March 2016) - Kaduk, James A.; Zhong, Kai; Gindhart, Amy M.; Blanton, Thomas N.
Abstract : The crystal structure of rivastigmine hydrogen tartrate has been solved and refined using synchrotron X-ray powder diffraction data, and optimized using density functional techniques. Rivastigmine hydrogen tartrate crystallizes in space group P 21 (#4) with a = 17.538 34(5), b = 8.326 89(2), c = 7.261 11(2) Å, β = 98.7999(2)°, V = 1047.929(4) Å 3, and Z = 2. The un-ionized end of the hydrogen tartrate anions forms a very strong hydrogen bond with the ionized end of another anion to form a chain. The ammonium group of the rivastigmine cation forms a strong discrete hydrogen bond with the carbonyl oxygen atom of the un-ionized end of the tartrate anion. These hydrogen bonds form a corrugated network in the bc -plane. Both hydroxyl groups of the tartrate anion form intramolecular O–H⋯O hydrogen bonds. Several C–H⋯O hydrogen bonds appear to contribute to the crystal energy. The powder pattern is included in the Powder Diffraction File ™ as entry 00-064-1501.